Downregulated Serum 14, 15-Epoxyeicosatrienoic Acid Is Associated With Abdominal Aortic Calcification in Patients With Primary Aldosteronism. Issue 4 (April 2018) - Liu, Pinming; Zhang, Shaoling; Gao, Jingwei; Lin, Ying; Shi, Guangzi; He, Wanbing; Touyz, Rhian M.; Yan, Li; Huang, Hui
Abstract : Patients with primary aldosteronism (PA) have increased risk of target-organ damage, among which vascular calcification is an important indicator of cardiovascular mortality. 14, 15-Epoxyeicosatrienoic acid (14, 15-EET) has been shown to have beneficial effects in vascular remodeling. However, whether 14, 15-EET associates with vascular calcification in PA is unknown. Thus, we aimed to investigate the association between 14, 15-EET and abdominal aortic calcification (AAC) in patients with PA. Sixty-nine patients with PA and 69 controls with essential hypertension, matched for age, sex, and blood pressure, were studied. 14, 15-Dihydroxyeicosatrienoic acid (14, 15-DHET), the inactive metabolite from 14, 15-EET, was estimated to reflect serum 14, 15-EET levels. AAC was assessed by computed tomographic scanning. Compared with matched controls, the AAC prevalence was almost 1-fold higher in patients with PA (27 [39.1%] versus 14 [20.3%]; P =0.023), accompanied by significantly higher serum 14, 15-DHET levels (7.18±4.98 versus 3.50±2.07 ng/mL; P <0.001). Plasma aldosterone concentration was positively associated with 14, 15-DHET (β=0.444; P <0.001). Multivariable logistic analysis revealed that lower 14, 15-DHET was an independent risk factor for AAC in PA (odds ratio, 1.371; 95% confidence interval, 1.145–1.640; P <0.001), especially in young patients with mild hypertension and normal body mass index. In conclusion, PA patients exibited more severe AAC, accompanied by higher serum 14, 15-DHET levels. On the contrary, decreased 14, 15-EET was significantly associated with AAC prevalence in PA patients, especially in those at low cardiovascular risk. Abstract : Supplemental Digital Content is available in the text.